The Effect of An Educational Program on Nurses’ Practices Regarding The Implementation of Patient Care and Safety Measures During Nasogastric Tube Feeding in The Critical Care Units in Syria - Abo Jeesh, Yaser Adnan; Mohammed Khalid, Elham Fath-Elalium; Ahmed Elbashier, Ishraqa Mohammed (European Scientific Journal, ESJ, 2021)
The intensive care unit (ICU) is considered a high- risk area in the hospital because of the severity of injuries and the high liability of occurrences associated with ICU. Critically ill patients are at high risk for actual or potential life-threating health problems. Moreover, critical care nurses must develop their knowledge, skills, and safe practice in acute areas where patients require more detailed observation or intervention to deliver safe and effective care. Objectives: This study aimed to assess the effect of an educational program on nurses’ practices regarding the implementation of patient care and safety measures during enteral feeding. Design: The quasi-experimental design was used in this study. Methods: The study was conducted from June to September 2020. All registered nurses who were working in the intensive care units during the period of data collection comprised the sample. Based on the nurses’ needs regarding the condition of their competencies during the initial assessment, we developed and designed the educational program. This program consists of two parts: theory and practical. The program contains workshop (8 hours) per day and educational pamphlet handout. The workshop consists of PowerPoint presentations, group discussions, and training scenarios. Results: This study was carried out with 48 nurses working in the previous intensive care units. The nurses’ score were improved after the program regarding to nurses’ age, qualification, and experience. The overall study found a statistically significant relationship of this procedure before and after the implementation of the educational program (p<0.001). Conclusion: There has been remarkable and variation improvement of nurses performance after they received the education program. The results show that a statistically significant difference was found before and after implementing the program regarding the nurses’ age, qualification, and experience. It is recommended to pay more attention to these nurses by helping them to improve their knowledge and practices in all nursing interventions. Furthermore, it is necessary to improve nurses’ awareness regarding the quality of care and patient safety. It was also found that the poor knowledge and practice and its complications have a negative impact on the quality of care and patient safety.